If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(c + 0.8) + 6 = 50 Reorder the terms: 5(0.8 + c) + 6 = 50 (0.8 * 5 + c * 5) + 6 = 50 (4 + 5c) + 6 = 50 Reorder the terms: 4 + 6 + 5c = 50 Combine like terms: 4 + 6 = 10 10 + 5c = 50 Solving 10 + 5c = 50 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 5c = 50 + -10 Combine like terms: 10 + -10 = 0 0 + 5c = 50 + -10 5c = 50 + -10 Combine like terms: 50 + -10 = 40 5c = 40 Divide each side by '5'. c = 8 Simplifying c = 8
| 4x^2-15x-54=0 | | -5Y+11=-4(2Y+4) | | -5-9=3w+7 | | -(20+d)= | | 2-x=15-x | | x^4-4x^2+2=0 | | -3x^2+8x=5 | | (n+1)(n+9)=0 | | 15x+4=13x+14 | | 5x^2-30x=0 | | -4.4s-2=-5.5s-42 | | 13+8(5x-9)=2 | | 4m+5=11+6 | | -4(10+4x)=-216 | | 7f=3f-52 | | -z+4z=-3z-4+8z | | 8(x+4)=52 | | 15h-9-6h=9 | | -5(-4-2x)=-70 | | t^2=9 | | 2(5-x)=26 | | 3(2w-1)-4w=27 | | 15x+15=12x-24 | | 63=9(x+3) | | 495=LWH | | 42+9c=16c | | -3(7-6x)=-39 | | =(1+9x)10 | | 2x^2+4x-6-x^2-3x-204=0 | | 4(4x-2)-10x=4 | | 0.1x+0.01x=0.11 | | one-third*(9b+1)=b-1 |